Bridging digital divide in creating knowledge society: a pilot project at Felcra Sri Makmur, Maran, Pahang Darul Makmur - Kaliannan, Maniam; S Chandran, Suseela Devi; Abd Rahim, Memiyanty (2011)
Malaysia is an industrially developing country. Poverty particularly among the rural people is one of the problems faced in the country. One of the causes of rural poverty is the digital divide between the rural and urban people, i.e. the rural people are disadvantaged compared to the urban because of their lack of knowledge, facilities and access to information communication technology (ICT) which are tools that can increase knowledge, productivity, collaborations and wealth (through global e-commerce and e-business). Although many Malaysians are exposed to ICT applications and have broadband access particularly the urbanites, many from the rural areas are still illiterate in these areas. This is because of many factors, e.g. the opportunity to access such technology such as Internet connection has not reached the remote villages located in the middle of the jungle e.g. the indigenous people ('Orang Asli'). Another reason may be the high cost of such technology which includes the cost of computers and Internet connection. The rural citizens are mostly estate workers and farmers; as such their income bracket makes it hard for them to afford such technology. Moreover, their low education level and poor command of English have caused them to be side lined in the digital world. Even if they are given access to computer technology and broadband access, they would not know how to use them as most of the ICT applications and Internet contents are in English. The main objective of this pilot study. is to introduce ICT and its functions to the rural community i.e. in this case will be the Orang Asli youth from FELCRA Sri Makmur, Maran, Pahang Darul Makmur. The aim is achieved by providing a five day training on various aspects of ICT at the public hall of FECLRA Sri Makmur with the help of Yayasan Pendidikan & Vokasional Wanita Malaysia (YPVWM). This action research is hoped to be an eye opener to the relevant authorities on the actual state of digital divide among Malaysians especially among the Orang Asli community, thus formulate right policy and action plan to reduce the digital divide and eventually close the digital divide gap among Malaysians by the year 2020.